Simple Controllable Fabrication of Novel Flower‐Like Hierarchical Porous NiO: Formation Mechanism, Shape Evolution and Their Application into Asymmetric Supercapacitors. Issue 16 (22nd July 2022) - Wei, Ying; Wu, Yuwei; Cao, Xiaoman; Cui, Luxia; Chen, Jiaqi; Wu, Qiong; Liu, Daliang; Sun, Zhijia; Zhang, Qingguo
Abstract: The rational tailoring of micro‐ and mesoporous distribution for porous transition metal oxide‐based nanomaterials is an important factor to control their electrochemistry performances. Herein, flower‐like hierarchical microspheres assembled by ultrathin nickel oxide (NiO) nanosheets were synthesized by a facile solvothermal route and subsequent annealing process. Theoretical analysis and experimental results demonstrate that NiO ultrathin nanosheets prepared by calcination at 450 °C (N‐450) have the optimal micro‐ and mesoporous distribution. The optimal microstructure provides plenty of ion transport channels and abundant active sites. As expected, the N‐450 electrode delivers an ultrahigh specific capacity of 546.53 F g −1 at a current density of 2 A g −1, which is greater than other electrodes. Remarkably, the assembled N‐450//AC asymmetric supercapacitor (ASC) achieves a high energy density of 29.7 Wh kg −1 (at a power density of 800 W kg −1 ) and exhibits an excellent cycling stability. This work demonstrates an available avenue to enhance the performance of supercapacitor by accurately controlling calcination temperature to adjust the porous architectures of ultrathin NiO nanosheets. Abstract : Calcination temperature as control condition is proposed to prepare flower‐like hierarchical microspheres assembled by ultrathin nickel oxide (NiO) nanosheets. The optimum micro‐mesoporous distribution and high surface area endow N‐450 with prominent electrical conductivity and abundant accessible active sites, therefore presenting ultrahigh specific capacity, good rate capability and superb electrochemical cyclability.